Association of autosomal‐recessive‐type distal renal tubular acidosis and Glanzmann thrombasthenia as a consequence of runs of homozygosity. Issue 7 (19th July 2022) - Aso, Keiko; Soutome, Takehiko; Satoh, Mari; Aoki, Takako; Ogura, Hiromi; Yamamoto, Toshiyuki; Kanno, Hitoshi; Takahashi, Hiroyuki
Abstract: We report the case of a Filipino girl with autosomal‐recessive‐type distal renal tubular acidosis and Glanzmann thrombasthenia caused by homozygous variants in the genes SLC4A1 and ITGA2B within the long homozygous DNA region on chromosome 17q21.31. This haplotype may be retained among individuals of Filipino descent. Abstract : We report the case of a Filipino girl with autosomal‐recessive‐type distal renal tubular acidosis and Glanzmann thrombasthenia owing to runs of homozygosity. Association of the two diseases could be life‐threatening. This haplotype may be retained among Filipinos.